2008
DOI: 10.1143/jjap.47.8565
|View full text |Cite
|
Sign up to set email alerts
|

Control of Electron Temperature by Varying DC Voltage to a Mesh Grid Blanketed with Thin Film in Plasmas

Abstract: Rubbing angle between rubbing direction and electrode of In-plane switching (IPS) mode, is a key factor deciding liquid crystal behavior. We have derived the solution of liquid crystal (LC) motion of non-zero rubbing angle under weak electric field for IPS mode. Dependence of electro-optical characteristics on rubbing angle of non-negligible size was analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…When e 1.16 eV T = and , probe characteristics are not changed as known from the experiments in Section 2. Actually, we confirmed the usefulness of this probe analysis even in the RF discharges at frequency of 13.56 MHz ( [32] [33] [35]).…”
Section: Assumptionsupporting
confidence: 68%
See 1 more Smart Citation
“…When e 1.16 eV T = and , probe characteristics are not changed as known from the experiments in Section 2. Actually, we confirmed the usefulness of this probe analysis even in the RF discharges at frequency of 13.56 MHz ( [32] [33] [35]).…”
Section: Assumptionsupporting
confidence: 68%
“…Argon plasma is generated by RF (25 MHz) discharge. A grid electrode G located at the outlet of the RF electrode is used for controlling the electron temperature in the downstream region of plasma [32]- [35]. The grid G (16 mesh/in.)…”
Section: Electron Temperature Measurement With Ion Acoustic Wave Methodsmentioning
confidence: 99%
“…Kato et al [7,8] performed experiments on controlling the electron temperature on plasmas passing through a mesh grid from a discharge region. Recently, they have showed that the grid bias method can be used for temperature control, even if the conductivity of the grid is reduced by the deposition of a dielectric diamond-like carbon film [9]. Bai et al also used mesh grid to control the electron temperature in the diffuse region of an inductively coupled plasma [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the control of e is of crucial importance for finding the best conditions of the chemical reactions necesary for the material processing [1][2][3][4]. In general, however, it is difficult to control e in weakly-ionized discharge plasmas, although several methods have been reported for the e control [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, we have already demonstrated that the grid bias method can still control e over a wide range [9]. In fact, high-quality diamond was produced in RF discharge CH 4 /H 2 plasmas [14], where e was decreased by varying mechaniclly the length of slits in plasmas [8].…”
Section: Introductionmentioning
confidence: 99%